Evaluating the impact of rehabilitation nursing intervention on quality of life in patients with burn injuries: A protocol for systematic review and meta-analysis - Xiang, Jun (Medicine (Baltimore), 2021)
BACKGROUND: Despite the availability of pharmacological intervention, patients with burn injuries experience pain during the treatment of wounds. Supplementary rehabilitation nursing intervention are required to enhance the wellbeing of patients sustaining injuries from burns. The present study aims to conduct a systematic exploration of the impact of rehabilitation nursing intervention on the wellbeing in patients sustaining burn injuries. METHODS: The electronic databases listed below will be searched systematically: PubMed, EMBASE, CINAHL, Cochrane Library, Web of Science, Scopus, China National Knowledge Infrastructure, and WanFang database. All the databases will be searched from their inauguration to November 2020. There will be no language constraints. Independent undertaking by 2 authors will select studies, extract data from selected studies, and assess the quality of the included studies. All disagreements will be resolved through discussion, or by consulting a third independent author. This study will make use of RevMan 5.3 software to perform statistical analysis. RESULTS: The present protocol summarizes high-quality evidence to assess the impact of rehabilitation nursing intervention on the wellbeing of patients sustaining burn injuries. CONCLUSION: The results of the present protocol has the potential to present evidence to assess whether rehabilitation nursing intervention can enhance the wellbeing of patients sustaining burn injuries. REGISTRATION NUMBER: November 17, 2020.osf.io/t6b8c/. (https://osf.io/t6b8c/).